Strategies for the separation of the furanic compounds HMF, DFF, FFCA and FDCA from Ionic liquids - Al,Ghatta A; Wilton-Ely,JDET; Hallett,JP (ACS Sustainable Chemistry & Engineering, 2019)
The catalytic upgrading of sugar derivatives into valuable building blocks represents an extremely important challenge intrinsic to the attempts to establish a green economy. However, the significance of separation and purification are often relegated to a marginal role or overlooked completely despite this aspect being critical for potential scale up. It is well established that the synthesis of 5-hydroxymethylfurfural (HMF) from sugars in ionic liquid media is a valuable, sustainable and high-yielding chemical pathway, but product separation has always remained an unresolved issue. In this contribution, the separation of HMF and three of its derivatives, 2,5-diformylfuran (DFF), 5-formyl-2-furancarboxylic acid (FFCA) and 2,5-furandicarboxylic acid (FDCA) from ionic liquids is analyzed. Various ionic liquids are screened in order to obtain an optimal separation process. The extraction of HMF is studied from the hydrophobic methyltrioctylammonium ionic liquids with water, obtaining a favorable partition coefficient for the aqueous phase. In contrast, its derivatives, DFF, FFCA and FDCA, can be easily separated by phase separation. DFF retains its sublimation attributes in the ionic liquid and can be readily separated in quantitative yields in high purity. This behavior is observed in ionic liquids but is not achievable in common organic solvents. FDCA and FFCA are separated by water addition and precipitation. It is found that less water is required for the precipitation of these compounds compared to dimethylsulfoxide (DMSO), which is a frequently employed reaction medium for their generation. The energy balance for regeneration of the ionic liquid after water addition is estimated using the enterprise ionic liquids database ILUAM. This study provides a set of solvent design guidelines for the selective synthesis, isolation and purification of these compounds in ionic liquids, aiding future reaction design.